Marginal cell layer in the buffalo hypophysis cerebri: A histological and immunohistochemical study - KHAN, MASSARAT; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2014)
The histomorphochemical study on adenohypophysis of 66 buffaloes of either sex aged from 1 week to adult revealed that the marginal cell layer lining the hypophyseal cleft comprised simple squamous, cuboidal or columnar type epithelium, which sometimes appeared pseudostratified. It was inconsistently ciliated. In general, the marginal epithelium stained pale but contained variably distributed PAS and alcian blue reactive cells. The cells positive to phloxin-B and illdehyde fuchsin, and those immunohistochemically reactive to FSH, LH, TSH, PRL, and GH also occurred within the marginal cell layer.